Physiological and growth responses to water deficit in the bioenergy crop Miscanthus x giganteus - Ings, Jennifer; Mur, Luis A.; Robson, Paul R.; Bosch, Maurice (Frontiers in Plant Science, 2013)
High yielding perennial biomass crops of the species Miscanthus are widely recognized as one of the most promising lignocellulosic feedstocks for the production of bioenergy and bioproducts. Miscanthus is a C4 grass and thus has relatively high water use efficiency. Cultivated Miscanthus comprises primarily of a single clone, Miscanthus x giganteus, a sterile hybrid between M. sacchariflorus and M. sinensis. M. x giganteus is high yielding and expresses desirable combinations of many traits present in the two parental species types; however, it responds poorly to low water availability. To identify the physiological basis of the response to water stress in M. x giganteus and to identify potential targets for breeding improvements we characterised the physiological responses to water-deficit stress in a pot experiment. The experiment has provided valuable insights into the temporal aspects of drought-induced responses of M. x giganteus. Withholding water resulted in marked changes in plant physiology with growth-associated traits among the first affected, the most rapid response being a decline in the rate of stem elongation. A reduction in photosynthetic performance was among the second set of changes observed; indicated by a decrease in stomatal conductance followed by decreases in chlorophyll fluorescence and chlorophyll content. Measures reflecting the plant water status were among the last affected by the drought treatment. Metabolite analysis indicated that proline was a drought stress marker in M. x giganteus, metabolites in the proline synthesis pathway were more abundant when stomatal conductance decreased and dry weight accumulation ceased. The outcomes of this study in terms of drought-induced physiological changes, accompanied by a proof-of-concept metabolomics investigation, provide a platform for identifying targets for improved drought-tolerance of the Miscanthus bioenergy crop.